2015
DOI: 10.1128/jvi.01792-15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibilities of Human Lung Primary Cells to H1N1 Influenza Viruses

Abstract: Human alveolar epithelial cells (AECs) and alveolar macrophages (AMs) are the first lines of lung defense. Here, we report that AECs are the direct targets for H1N1 viruses that have circulated since the 2009 pandemic (H1N1pdm09). AMs are less susceptible to H1N1pdm09 virus, but they produce significantly more inflammatory cytokines than AECs from the same donor. AECs form an intact epithelial barrier that is destroyed by H1N1pdm09 infection. However, there is significant variation in the cellular permissivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…We believe that these variations may have been due to variability in monocytes obtained from blood donors. Consistent with our findings, several previous studies have also reported that variability in susceptibility to infection and/or innate immune responses may arise due to variations in genetic and epigenetic background of each blood donor (71)(72)(73).…”
Section: Discussionsupporting
confidence: 81%
“…We believe that these variations may have been due to variability in monocytes obtained from blood donors. Consistent with our findings, several previous studies have also reported that variability in susceptibility to infection and/or innate immune responses may arise due to variations in genetic and epigenetic background of each blood donor (71)(72)(73).…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have reported a detrimental role for IL-1b for severe influenza infections (36)(37)(38). We recently also reported that IL-1b treatment reduces the transepithelial electrical resistance of human primary alveolar epithelial cells and leads to epithelial barrier injury (19). In this study, accompanied by the striking reduction in inflammasome activation (Figs.…”
Section: Aim2 Deficiency Provides Protection Against Iav-induced Lungmentioning
confidence: 51%
“…Deidentified patient lungs that were not suitable for transplantation and donated for medical research were obtained through the International Institute for the Advancement of Medicine (Edison, NJ) and the Airway Epithelial Core at the University of Pittsburgh as we described previously (17,19 , and wild-type (WT) C57BL/6J mice were purchased from The Jackson Laboratory (Bar Harbor, ME); ASC 2/2 mice were from Genentech (San Francisco, CA). All mice were bred inhouse, and AIM2 2/2 mice were further backcrossed with C57BL/6J mice for two more generations.…”
Section: Human Lung Donorsmentioning
confidence: 99%
See 2 more Smart Citations